Assemblies of Colloidal CdSe Tetrapod Nanocrystals with Lengthy Arms for Flexible Thin-Film Transistors - Heo, Hyeonjun; Lee, Moo Hyung; Yang, Jeehye; Wee, Han Sol; Lim, Jaehoon; Hahm, Donghyo; Yu, Ji Woong; Bae, Wan Ki; Lee, Won Bo; Kang, Moon Sung; Char, Kookheon (AMER CHEMICAL SOC, 2017)
Herein, we report unique features of the assemblies of tetrapod-shaped colloidal nanocrystals (TpNCs) with lengthy arms applicable to flexible thin-film transistors. Due to the extended nature of tetrapod geometry, films made of the TpNC assemblies require reduced numbers of inter-NC hopping for the transport of charge carriers along a given channel length; thus, enhanced conductivity can be achieved compared to those made of typical spherical NCs without arms. Moreover, electrical conduction through the assemblies is tolerant against mechanical bending because interconnections between TpNCs can be well-preserved under bending. Interestingly, both the conductivity of the assemblies and their mechanical tolerance against bending are improved with an increase in the length of tetrapod arms. The arm length-dependency was demonstrated in a series of CdSe TpNC assemblies with different arm lengths (l = 0-90 nm), whose electrical conduction was modulated through electrolyte gating. From the TpNCs with the longest arm length included in the study (l = 90 nm), the film conductivity as high as 20 S/cm was attained at 3 V of gate voltage, corresponding to electron mobility of >10 cm(2)/(V s) even when evaluated conservatively. The high channel conductivity was retained (similar to 90% of the value obtained from the flat geometry) even under high bending (bending radius = 5 mm). The results of the present study provide new insights and guidelines for the use of colloidal nanocrystals in solution-processed flexible electronic device applications.
Keywords: FIELD-EFFECT TRANSISTORS; ELECTRICAL-TRANSPORT; CHARGE-TRANSPORT; SOLAR-CELLS; SOLIDS; PHOTODETECTORS; PHOTOVOLTAICS; PROSPECTS; LIGANDS; HALIDE